A method for characterizing the equiaxed degree of titanium alloy grains
By applying electron backscattering and diffraction technology (EBSD) combined with polishing treatment in titanium alloys, the equiaxiality of titanium alloy α grains is quantitatively characterized, and the problem of low detection accuracy in the existing technology is solved, and the accuracy of the performance of titanium alloy is achieved. Evaluate.
Patent Information
- Application Number
- CN202110209317.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-02-24
- Publication Date
- 2025-02-21
- Estimated Expiration
- 2041-02-24
AI Technical Summary
The prior art is difficult to accurately and quantitatively characterize the equiax or equiax of titanium alloy alpha grains, resulting in low detection accuracy and the inability to accurately evaluate the performance of titanium alloys.
Electron backscattering diffraction technology (EBSD) combined with electrolysis or mechanical polishing treatment, scan and analyze titanium alloy samples to calculate the average aspect ratio and equiaxization uniformity of the grains, thereby quantitatively characterizing the equiax of the grains, etc. Axillation uniformity and spheroidization rate.
It realizes fast, accurate and automatic statistics of the isoxiality of α and β grains in titanium alloys, improves detection accuracy, and the results can be quantitative, repeatable and statistically significant, and can be used to evaluate the performance of titanium alloys and provide scientific guidance.
Smart Images

Figure BDA0002950811890000031 
Figure BDA0002950811890000033 
Figure BDA0002950811890000035
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of metal material microstructure characterization, and particularly relates to a titanium alloy grain equiaxivity characterization method. Background Art
[0002] Titanium alloy has various excellent properties, such as low density, high specific strength, corrosion resistance, good high and low temperature resistance, non-magnetic and non-toxic. It is another important structural material after steel and aluminum. At present, titanium alloy has been widely used in many fields such as aerospace, aviation, navigation, petroleum, chemical industry, light industry, metallurgy, machinery, medical treatment and energy. Traditional dual-structure titanium alloy requires equiaxial grains. Deformation at the temperature of the β zone and (α+β) zone will cause changes in the shape of the grains. When the low-magnification structure is in a plane parallel to the direction of the force, the equiaxial grains become ellipsoidal. Non-equiaxial grains will produce anisotropy and significantly reduce some key mechanical performance parameters. Therefore, the equiaxiality of the grains of dual-structure titanium alloys is of great significance.
[0003] At present, there is a relatively mature test method for grain size (GBT 6394-2017 Method for Determining Average Grain Size of Metals), but for dual-structure titanium alloys, the structure is generally composed of various forms of α grains distributed on the transformed β or β matrix. The size, shape, and equiaxed degree of the α phase will affect its performance. For example, for fracture toughness, general equiaxed α grains are not the best choice. Equiaxed α grains with a certain aspect ratio are of great significance for improving the damage tolerance and impact performance of titanium alloys.
[0004] Chinese patent CN107367510A discloses "a method for determining the equiaxed crystal ratio of high carbon steel continuous casting billets". In this method, the equiaxed crystal area is manually identified and the image is specially processed to measure the equiaxed crystal percentage. This method needs to be processed based on the metallographic structure image, and then the aspect ratio of each individual grain is measured manually to determine whether it is an equiaxed grain. Its disadvantage is that it uses manual selection of grains and measurement of length and width, which has high errors and is time-consuming and labor-intensive.
[0005] In addition, there is a non-standard method that uses the comparison method to test. This method generally prepares standard images with different isoaxiality that are evenly distributed for a specific metal material, and compares the tissue image of the sample to be tested with the standard image to obtain the isoaxiality. The advantage of this method is that it is relatively fast, but the evaluation level can only cover a range in the standard image, and it is impossible to quantitatively characterize the isoaxiality.
[0006] Recently, with the development of electron backscatter diffraction technology (EBSD), it has been increasingly applied to the field of material characterization. For example, Chinese patent CN104090033A discloses "A method for establishing a simulation model of FDTD ultrasonic detection of coarse-grained materials based on EBSD spectra". It is a method proposed by Lei Mingkai and others from Dalian University of Technology to use electron backscatter diffraction technology (EBSD) to accurately and efficiently measure the grain structure of austenitic stainless steel.
[0007] However, there is currently no method reported that can accurately and quantitatively characterize the equiaxity or equiaxity ratio of α grains in titanium alloys. Summary of the invention
[0008] The purpose of the present invention is to provide a method for characterizing the equiaxicity of titanium alloy grains, which can quantitatively characterize the equiaxicity of grains, equiaxed uniformity and spheroidization rate, and can quickly, accurately and automatically count the equiaxicity of grains in titanium alloys, improve the detection accuracy, and the results are quantitative, repeatable and statistically significant. In addition, the equiaxicity, equiaxed uniformity and spheroidization rate of α and β grains can be quantitatively characterized respectively, and the results can be used to characterize the relationship between the various properties of titanium alloys, and provide scientific guidance for titanium alloy processing technology or other needs.
[0009] To achieve the above object, the technical solution adopted by the present invention is as follows:
[0010] A method for characterizing the equiaxicity of α-grains of titanium alloy, characterized by comprising:
[0011] 1) Sample preparation
[0012] Mount and roughly polish the cut specimens to ensure that the surface to be tested is flat and parallel to the bottom surface;
[0013] 2) Polishing
[0014] Electrolytic polishing or mechanical polishing is used to relieve stress on the surface of the sample to be tested;
[0015] 3) EBSD detection
[0016] Fix the polished sample on the sample stage, ensure that the angle between the EBSD probe plane and the surface to be tested is 65-75°, set the acceleration voltage to 15-20KV, adjust the magnification to select the analysis area, ensure that the number of grains in the observation field is ≥100, and control the scanning step length to ≤1 / 3 of the minimum grain size; obtain the grain orientation imaging map, the number of grains and the aspect ratio of each grain in the analysis area by scanning the diffraction pattern of the analysis area;
[0017] 4) Data analysis
[0018] The average aspect ratio of the grains is calculated using the above-mentioned test data, the average aspect ratio is used to define and characterize the equiaxed degree, and the equiaxed uniformity is calculated; the calculation formula of the average aspect ratio is as follows:
[0019]
[0020] Where:
[0021] Average aspect ratio;
[0022] n, number of grains;
[0023] n i , the aspect ratio of a single grain;
[0024] The calculation formula of the equiaxed uniformity is as follows:
[0025]
[0026] Where:
[0027] S 2 (P i ), isometric uniformity;
[0028] P i , the aspect ratio of a single grain;
[0029] Average aspect ratio;
[0030] n, number of grains.
[0031] Furthermore, the grain spheroidization rate is used to characterize the spheroidization degree of the grains, and the calculation formula of the grain spheroidization rate is as follows:
[0032]
[0033] Where:
[0034] σ, grain spheroidization rate;
[0035] n u , the number of grains with aspect ratio less than or equal to 3;
[0036] n, total number of grains.
[0037] Preferably, in step 1), when the sample is taken from a rod, it should be taken from a cross section at 1 / 4 to 3 / 4 of the rod radius.
[0038] Preferably, in step 1), when the sample is taken from a plate or profile, a cross section at 1 / 4 to 3 / 4 of the thickness or length of the plate or profile should be taken.
[0039] Preferably, the polishing liquid used for the electrolytic polishing is a 5-15% perchloric acid anhydrous ethanol solution, the polishing voltage is 32-38V, the polishing current is 0.2-0.6A, and the polishing time is 30-50s. After the electrolytic polishing is completed, the sample is placed in anhydrous ethanol solution for 10s and repeatedly cleaned until no polishing liquid remains on the surface.
[0040] Preferably, the polishing liquid is cooled to 2-10° C. with liquid nitrogen before use.
[0041] Preferably, the mechanical polishing is performed by grinding with sandpaper of No. 100 to No. 2000 in sequence, and then polishing with a silicone latex polishing liquid, with a polishing pressure of 2 to 8N and a polishing time of 1 to 2.5 hours.
[0042] Preferably, the mechanical polishing time is 2 to 2.5 hours.
[0043] Preferably, the polishing disc used for the mechanical polishing is made of woven cloth.
[0044] The present invention uses EBSD scanning technology to measure and count the grain information in the analysis area of the titanium alloy sample, so that the number of all grains in the analysis area of the titanium alloy and their aspect ratio can be measured quickly and accurately, so that the grain equiaxity, equiaxed uniformity and spheroidization rate can be quantitatively characterized. EBSD scanning technology can distinguish α grains and β grains in the titanium alloy organization from the perspective of crystal structure, so as to quickly and accurately count the equiaxity of α grains and β grains in the titanium alloy, improve the detection accuracy, and the results are quantitative, repeatable and statistically significant.
[0045] The present invention uses the average aspect ratio to characterize and define the degree of equiaxed grains. Compared with the image comparison method, it can quantitatively characterize the degree of equiaxed grains, so it is more accurate. The smaller the average aspect ratio, the higher the equiaxed degree of the grains, that is, the more fully spheroidized the structure. In addition, the equiaxed uniformity of the grain aspect ratio can be used to represent the discreteness of the equiaxed degree. The larger the value, the greater the difference in the degree of equiaxed grains between different grains, and the smaller the value, the more uniform the equiaxed grains. Further, the degree of spheroidization of the grains can be calculated, and grains with an aspect ratio greater than 3 are defined as non-spheroidized grains.
[0046] According to the grain equiaxity, equiaxed uniformity and spheroidization degree in the titanium alloy structure, the relationship between the various properties of the titanium alloy can be characterized, providing scientific guidance for titanium alloy processing technology or other needs.
[0047] In the present invention, when preparing the sample, when the sample is taken from a rod, it should be taken from the cross section at 1 / 4 to 3 / 4 of the rod radius, and when the sample is taken from a plate or profile, it should be taken from the cross section at 1 / 4 to 3 / 4 of the thickness or length of the plate or profile. The standard planes at these positions can represent the typical tissue morphology of the sample to be tested. After the sample is cut, it is inlaid and roughly polished to ensure that the surface of the sample to be tested is flat and parallel to the bottom surface.
[0048] The surface of the sample to be tested also needs to be stress relieved, which can be done by electrolytic polishing or mechanical polishing. The polishing liquid used for electrolytic polishing is 5-15% perchloric acid anhydrous ethanol solution, the polishing voltage is 32-38V, the current is 0.2-0.6A, and the polishing time is 30-50s. After the electrolytic polishing is completed, the sample is repeatedly cleaned in anhydrous ethanol solution for 10s until there is no polishing liquid residue on the surface. The EBSD resolution rate of ordinary dual-state titanium alloy samples prepared by this electrolytic polishing can reach 90% or more. Mechanical polishing uses sandpaper from No. 100 to No. 2000 in sequence, and then polishes with silicone latex polishing liquid. The polishing pressure is 2-8N, and the polishing disc is made of woven cloth or other suitable materials. The polishing time is 1-2.5h, preferably 2-2.5h. After mechanical polishing for 1h, the EBSD resolution rate can reach 85% or more, and after the polishing time reaches 2h, the EBSD resolution rate can reach 94% or more.
[0049] When the present invention performs EBSD scanning on a sample, the analysis area and the appropriate magnification are set according to the different grain sizes on the surface of the sample to be detected, so that the observation field includes at least 100 grains to ensure that the result has statistical significance.
[0050] The present invention selects a suitable scanning step size according to the minimum grain size that needs to be detected in the sample. The scanning step size is the distance that the electron beam moves on the sample surface when receiving the diffraction Kikuchi band signal. The smaller the scanning step size, the higher the signal resolution rate on the sample surface, but the corresponding speed will be slower; the larger the scanning step size, the lower the resolution rate, but the scanning speed will be faster. Selecting different scanning step sizes in the EBSD experiment will produce different results. If the size of a single grain is smaller than the scanning step size, the grain boundary of the grain cannot be detected because the smaller grains "dissolve" into the adjacent grain boundaries, increasing the actual average grain size. Figure 1 As shown in the figure, the grains just fall into the scanning step range and cannot be detected; if the average grain size is slightly larger than the scanning step, the grains can be distinguished, but the grain boundary determination is not accurate, which will increase the grain size error, such as Figure 2 As shown in Figure 1, the detected area of the grain (the area within the red line) is much smaller than the actual area; the grain area can only be effectively detected when the grain size is much larger than the scanning step length, such as Figure 3 Only when the scanning step size is controlled to be less than or equal to 1 / 3 of the minimum grain size, the actual grain area can be effectively detected.
[0051] Beneficial effects of the present invention:
[0052] The present invention uses EBSD technology to measure the number and aspect ratio of grains in titanium alloy structure. Compared with the prior art of manually measuring the aspect ratio of each grain using metallographic structure photos, the measurement is faster and more accurate, and the analysis accuracy, analysis time and analysis area can be adjusted by setting parameters to meet the requirements of different scenarios.
[0053] In addition, the EBSD technique can be used to distinguish the α and β grains in the titanium alloy organization from the perspective of crystal structure, so that the equiaxity, equiaxed uniformity and spheroidization rate of the α and β grains can be quantitatively characterized respectively, and the equiaxity of the α grains in the titanium alloy can be quickly and accurately counted to improve the detection accuracy. Compared with the prior art of determining the degree of equiaxed by establishing an equiaxed map or using a comparison method, the results are quantitative, repeatable and statistically significant. The results can be used to characterize the relationship between the various properties of titanium alloys and provide scientific guidance for titanium alloy processing technology or other needs. BRIEF DESCRIPTION OF THE DRAWINGS
[0054] Figure 1 Schematic diagram of a scan with a step size larger than the size of a single grain.
[0055] Figure 2 Schematic diagram of the scanning step size close to the size of a single grain.
[0056] Figure 3 Schematic diagram of a scan step size smaller than the size of a single grain.
[0057] Figure 4 Grain orientation imaging diagram of samples No. 1 and No. 2 in Example 1 of the present invention.
[0058] Figure 5 Phase distribution diagram of samples No. 1 and No. 2 in Example 1 of the present invention.
[0059] Figure 6 This is the grain orientation imaging diagram of samples No. 3 and No. 4 in Example 2 of the present invention.
[0060] Figure 7 This is the α phase distribution diagram of samples No. 3 and No. 4 in Example 2 of the present invention.
[0061] Figure 8 This is a comparison diagram of the area percentage distribution of α grains with different equiaxes of samples No. 3 and No. 4 in Example 2 of the present invention.
[0062] Fig. 9 This is a comparison diagram of the number distribution of α grains with different equiaxes of samples No. 3 and No. 4 in Example 2 of the present invention. DETAILED DESCRIPTION
[0063] The present invention will be further described below in conjunction with the embodiments and drawings.
[0064] Example 1
[0065] 1) Sample preparation
[0066] Take two block specimens from the cross section at 1 / 2 radius of the titanium alloy bar sample, mark them as specimen No. 1 and specimen No. 2, the cross-sectional size of the specimen is 10×10mm, and they are inlaid and polished to ensure that the surface of the specimen to be tested is flat and parallel to the bottom surface;
[0067] 2) Polishing
[0068] The surface of the sample to be tested was subjected to electrolytic polishing to relieve stress, with a voltage of 35V, a current of 0.4A, and a polishing time of 40s. After polishing, the sample was placed in anhydrous ethanol solution for 10s and repeatedly cleaned until no polishing liquid remained on the surface;
[0069] 3) EBSD detection
[0070] A clean and stress-free sample was attached to the sample stage with conductive tape, and the EBSD probe plane was ensured to be at an angle of 70° with the sample surface to be tested to obtain the strongest pattern signal. The acceleration voltage was set to 20KV, the analysis area was selected, the magnification was 1000x, and the scanning step was selected to be 0.1μm. After the analysis area was scanned, the grain orientation distribution map and phase distribution map of the sample were obtained. Figure 4 The grain orientation distribution diagram of sample No. 1 and sample No. 2 of the present invention is shown in FIG. Figure 5 This is the phase distribution diagram of sample No. 1 and sample No. 2 of the present invention.
[0071] 4) Data analysis
[0072] The α grain aspect ratio data in the original data were statistically analyzed, and the extremely small α grains with a grain size less than 1 μm were filtered out according to actual needs. Then, the average aspect ratio, equiaxed uniformity and spheroidization rate of the α grains of sample No. 1 and sample No. 2 were calculated respectively. The specific data are shown in Table 1.
[0073] Table 1
[0074]
[0075] The equiaxed degree of sample No. 1 is less than that of sample No. 2, indicating that the equiaxed degree of sample No. 1 is higher and the microspheroidization is more complete; while the equiaxed uniformity of sample No. 1 is lower than that of sample No. 2, indicating that the equiaxed uniformity of sample No. 1 is slightly higher. The spheroidization rate of sample No. 1 is 88.2% and that of sample No. 2 is 94.1%. It can be seen that although the equiaxed degree of sample No. 2 is lower, the spheroidization rate is higher.
[0076] Figure 4Different gray levels represent different grain orientations, while Figure 5 The grayish white is the α phase, and the rest is the β phase. It can be seen that the equiaxed state of the two samples is similar, and both contain a certain amount of equiaxed α and secondary α (short strips). It is difficult to determine the equiaxed degree or spheroidization degree of sample 1 and sample 2 from the figure, but after data analysis, a detailed comparison can be made.
[0077] Example 2
[0078] 1) Sample preparation: Take two block samples from the cross section at 1 / 2 radius of the titanium alloy bar, mark them as sample No. 3 and sample No. 4, the sample cross-section size is 10×10mm, and they are inlaid and polished to ensure that the surface of the sample to be tested is flat and parallel to the bottom surface;
[0079] 2) Polishing
[0080] The surface of the sample to be tested was subjected to electrolytic polishing to relieve stress, with a voltage of 35V, a current of 0.4A, and a polishing time of 40s. After polishing, the sample was repeatedly cleaned in anhydrous ethanol solution until no polishing liquid remained on the surface;
[0081] 3) EBSD detection
[0082] A clean and stress-free sample was attached to the sample stage with conductive tape, and the EBSD probe was ensured to be at an angle of 70° to the sample surface to obtain the strongest pattern signal. The acceleration voltage was set to 20 KV, the analysis area was selected, the magnification was 1000x, and the scanning step was selected to be 0.1 μm. After the analysis area was scanned, the grain orientation distribution map and phase distribution map of the sample were obtained. In this embodiment, Figure 6 The grain orientation distribution diagram of sample No. 3 and sample No. 4 of the present invention is shown in FIG. Figure 7 Phase distribution diagram of sample No. 3 and sample No. 4 of the present invention;
[0083] 4) Data analysis
[0084] The α grain aspect ratio data in the original data were statistically analyzed. First, the extremely small α grains with a grain size less than 1 μm were filtered out according to actual needs, and then the average aspect ratio, equiaxed uniformity and spheroidization rate of the α grains of the two samples were calculated respectively.
[0085] from Figure 6 and Figure 7 It can be seen that the distribution morphology of the α phase is slightly different. In order to better describe this morphological difference, it can be characterized by the isoaxiality percentage content distribution diagram and the isoaxiality quantity distribution diagram.
[0086] Figure 8This is the distribution diagram of the percentage content of α grains with different equiaxes for samples No. 3 and No. 4. It can be seen that most of the α grain areas of samples No. 3 and 4 are distributed in the equiaxeity interval of 2. The difference is that sample No. 4 has more grains distributed in the equiaxeity interval of 2, indicating that its distribution is more concentrated.
[0087] Fig. 9 Figure 3 shows the distribution of α grains with different equiaxes for samples 3 and 4. It can be seen that most of the α grains of the two samples are distributed in the interval of equiaxes of 1. The number of grains in the interval of equiaxes of 1 for sample 3 is larger. Figure 6 By comparison, it can be seen that although the number of grains in the equiaxed range of 1 for samples No. 3 and No. 4 is large, their area share is very small.
Claims
1. A method for characterizing the equiaxivity of titanium alloy grains, characterized in that: include: 1) Sample preparation; Mount and roughly polish the cut specimens to ensure that the surface to be tested is flat and parallel to the bottom surface; 2) Polishing Electrolytic polishing or mechanical polishing is used to relieve stress on the surface of the sample to be tested; 3) EBSD testing Fix the polished sample on the sample stage, ensure that the angle between the EBSD probe plane and the surface to be tested is 65-75°, set the acceleration voltage to 15-20KV, adjust the magnification to select the analysis area, ensure that the number of grains in the observation field is ≥100, and control the scanning step length to ≤1 / 3 of the minimum grain size; obtain the grain orientation imaging map, the number of grains and the aspect ratio of each grain in the analysis area by scanning the diffraction pattern of the analysis area; 4) Data analysis The average aspect ratio of the grains is calculated using the above-mentioned test data, the average aspect ratio is used to define and characterize the equiaxed degree, and the equiaxed uniformity is calculated; the calculation formula of the average aspect ratio is as follows: Where: Average aspect ratio; n: number of grains; n i : is the aspect ratio of a single grain; The calculation formula of the equiaxed uniformity is as follows: Where: S 2 (n i ), isometric uniformity; n i , the aspect ratio of a single grain; Average aspect ratio; n: number of grains.
2. The method for characterizing the equiaxivity of titanium alloy grains according to claim 1, characterized in that: The grain spheroidization rate is used to characterize the spheroidization degree of the grains. The calculation formula of the grain spheroidization rate is as follows: Where: σ, grain spheroidization rate; n u , the number of grains with aspect ratio less than or equal to 3; n, total number of grains.
3. The method for characterizing the equiaxivity of titanium alloy grains according to claim 1, characterized in that: In step 1), when the sample is taken from a rod, it should be taken from a cross section at 1 / 4 to 3 / 4 of the rod radius.
4. The method for characterizing the equiaxivity of titanium alloy grains according to claim 1, characterized in that: In step 1), when the sample is taken from a plate or profile, a cross section at 1 / 4 to 3 / 4 of the thickness or length of the plate or profile should be taken.
5. The method for characterizing the equiaxivity of titanium alloy grains according to claim 1, characterized in that: The polishing liquid used for the electrolytic polishing is a 5-15% perchloric acid anhydrous ethanol solution, the polishing voltage is 32-38V, the polishing current is 0.2-0.6A, and the polishing time is 30-50s. After the electrolytic polishing is completed, the sample is placed in anhydrous ethanol solution for 10s and repeatedly cleaned until no polishing liquid remains on the surface.
6. The method for characterizing the equiaxivity of titanium alloy grains according to claim 5, characterized in that: The polishing liquid is cooled to 2-10° C. with liquid nitrogen before use.
7. The method for characterizing the equiaxivity of titanium alloy grains according to claim 1, characterized in that: The mechanical polishing is performed by using sandpaper of No. 100 to No. 2000 in sequence, and then polishing is performed with a silicone latex polishing liquid, the polishing pressure is 2 to 8N, and the polishing time is 1 to 2.5 hours.
8. The method for characterizing the equiaxivity of titanium alloy grains according to claim 7, characterized in that: The mechanical polishing time is 2 to 2.5 hours.
9. The method for characterizing the equiaxivity of titanium alloy grains according to claim 1, 7 or 8, characterized in that: The polishing disc used for the mechanical polishing is made of woven cloth.
Citation Information
Patent Citations
Method for establishing FDTD (Finite Difference Time Domain) ultrasonic detection simulation model of coarse crystal material based on EBSD (Electron Back-Scattered Diffraction) spectrum
CN104090033A
Method for determining equiaxed crystal proportion of high-carbon steel continuous casting billet
CN107367510A
Method for rapidly measuring and finely classifying full-form crystal grains of steel material
CN103940708A
Hot-rolled steel sheet having excellent surface hardness after carburizing heat treatment and excellent cold workability
CN105658829A